Chronic Sodium Selenate Treatment Restores Deficits in Cognition and Synaptic Plasticity in a Murine Model of Tauopathy - Ahmed, Tariq; Van der Jeugd, Ann; Caillierez, Raphaëlle; Buée, Luc; Blum, David; D’Hooge, Rudi; Balschun, Detlef (Frontiers in Molecular Neuroscience, 2020)
A major goal in diseases is identifying a potential therapeutic agent that is cost-effective and can remedy some, if not all, disease symptoms. In AD, aggregation of hyperphosphory¬lated tau protein is one of the neuropathological hallmarks and Tau pathology correlates better with cognitive impairments in AD patients than amyloid ß load, supporting a key role of tau-related mechanisms. Selenium is a non-metallic trace element that is incorporated in the brain into selenopro¬teins. Chronic treatment with sodium selenate, a non-toxic selenium com¬pound, was recently reported to rescue behavioral phenotypes in tau mouse models. Here we focused on the effects of chronic selenate application on synaptic transmission and synaptic plasticity in THY-Tau22 mice, a transgenic animal model of tauopathies. Three months with a supplement of sodium selenate in the drinking water (12µg/ml) restored not only impaired neurocognitive functions, but also rescued long-term depression, a major form of synaptic plasticity. Furthermore, selenate reduced the inactive demethylated catalytic subunit of protein phosphatase 2A (PP2A) in THY-Tau22 without affecting total PP2A. Our study provides evidence that chronic dietary selenate rescues functional synaptic deficits of tauopathy and identifies an activation of PP2A as the putative mechanism.